Rights of the Indegenous Peoples Related to Land Acquisition: A Comparative Analysis between Malaysia and the Philiphines: (Hak Orang Asal Berkaitan dengan Pengambilalihan Tanah: Kajian Perbandingan antara Malaysia dengan Filipina) (Kanun: Jurnal Undang-undang Malaysia, 2021)
The Orang Asli are in a precarious position compared to other majority groups in Peninsular Malaysia as their customary land rights are continuously infringed upon. This is worrying because land is a vital part of the Orang Asli livelihood. Several issues regarding the provisions of native land rights, acquisition of Orang Asli ancestral land not in line with correct procedure, and issues concerning compensation for any acquisition of ancestral land are the main problems faced by the Orang Asli. Hence, the main objective of this research is to examine the legal rights of the Orang Asli to their ancestral land in Peninsular Malaysia, to throw light on the correct procedure of acquisition of such according to legal provisions, and to compare and contrast acquisition of native ancestral land in Peninsular Malaysia to that in the Philippines. Through a doctrinal and comparative approach, this research hopes to enhance knowledge regarding Orang Asli customary rights to land and land acquisition in Peninsular Malaysia, as well as to aid law-makers to reform existing laws and policies in order to ensure protection of Orang Asli rights in the future.Keywords: Orang Asli, customary land rights, procedure for extinguishment, compare